Pengaruh Job Enrichment terhadap Employee Engagement melalui Psychological Meaningfulness sebagai Mediator - Sungkit, Flavia Norpina; Meiyanto, IJK Sito (Gadjah Mada Journal of Psychology, 2015)
The purpose of the study is to investigate the influence of job enrichment toward employee engagement through psychological meaningfulness as the mediator. Research design used is a cross-sectional study of 112 employees. Data is analyzed by multiple linear regression analysis. Result shows job enrichment is able to influence employee engagement significantly through psychological meaningfulness as the mediator. The p=0,000 with significance level 0,05. The sig F change shows 0,006, which is<0,05, therefore mediation effect is significant. Mediation effect also has a better influence than the direct effect. The effect is increasing from 27,2% without mediator to 31,5% with mediator.Keywords: employee engagement, psychological meaningfulness, job enrichment